(3GdNHQ GdJGe aj MOhO GdCQV GdebOSI hGdTGes - (3GdJeQJGTj , UGdM Hf CMeO GdJeQJGTj GdYeQj, GdZRj,J (B1127 (3g` s ((3UGdM Hf CMeO GdfhjQi GdeGdci GdZRi GdYbjdj s)
(3ChdgG (B:s
(3ef GdMce hGdYde hGdcQe YXje GdTje hGdSYGOI GdeDHOI MVQI ehdGfG GdhRjQ s
(3BNQgG (B:s
(3hef LgI GdZQH GdOjGQ GdeUQjI heedcI GdZQH heG hGdGgG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B188s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs